Rigorism of truth : "Moses the Egyptian" and other writings on Freud and Arendt - Blumenberg, Hans; Meyer, Ahlrich, 1941-; Kroll, Joe Paul, 1979- (Ithaca : Cornell University Press : Cornell University Library, 2018)
"In 'Moses the Egyptian'--the centerpiece of this book--the German philosopher Hans Blumenberg addresses two defining figures in the intellectual history of the twentieth century: Sigmund Freud and Hannah Arendt"--Provided by publisher.
Frontmatter -- Contents -- I Moses the Egyptian -- II Excerpts and Preliminary Studies -- III Thematically Related Texts from the Nachlass -- Editor’s Afterword -- Editorial Note and Acknowledgments -- Translator’s Note -- Illustration Credits -- About the Authors.
Includes bibliographical references.
Online resource; title from digital title page (viewed on March 05, 2018).
JSTOR
Keywords: Moses -- (Biblical leader); Freud, Sigmund, -- 1856-1939.; Arendt, Hannah, -- 1906-1975.; Arendt, Hannah, -- 1906-1975.; Freud, Sigmund, -- 1856-1939.; Moses, -- (Biblical leader); Moses -- (Biblical leader); Eichmann in Jerusalem (Arendt, Hannah); Mann Moses und die monotheistische Religion (Freud, Sigmund); PHILOSOPHY -- History & Surveys -- Modern; PHILOSOPHY -- Epistemology